Immunomodulatory and Tissue-preserving Effects of Human Dental Follicle Stem Cells in a Rat Cecal Ligation and Perforation Sepsis Model - GÜL, FETHİ; AKKOÇ, TUNÇ; CİNEL, ZELİHA LEYLA (ELSEVIER SCIENCE INC, 2020)
Background. Mesenchymal stem cells may be used for the treatment of sepsis. Dental follicle stem cells (DFSCs) are easily accessible but have not been studied in vivo or in clinical trials in sepsis models. Aim of the study. We aim to elucidate DFSC effects on host immunological functions in a rat cecal ligation and perforation (CLP) sepsis model. Methods. Adult male rats were categorized into group 1 (sham procedure SP), group 2 (SP + 1 x 10(6) DFSCs administered 0 h after SP), group 3 (CLP + saline), group 4 (CLP 1 x 10(6) DFSCs administered 0 h after CLP), and group 5 (CLP + 1 x 10(6) DFSCs administered 4 h after CLP). Green fluorescent protein-labeled cells were used for imaging. Histopathological examination of ileal tissues was performed. Results. A significant increase in the percentage of CD4+/CD25+/Foxp3+ Treg cells in groups 4 and 5 occurred compared with that in group 3. No significant changes in CD3+/CD4+ helper T-cells and CD3+/CD8+ cytotoxic T-cells were observed. Treatment with DFSCs at 4 h significantly decreased the level of TNF-alpha compared with that in group 3. No significant changes in IL-10 levels and lymphocyte proliferation suppression were observed. During histopathological examination, no high scoring (Chiu scores: 3 or 4) rats were observed in the curative treatment group (group 5). Conclusions. Treatment with DFSC after 4 h of sepsis induction downregulates tissue inflammatory responses by decreasing TNF-alpha levels and increasing Treg cell ratio. This also has a protective effect on intestinal tissues during sepsis. (C) 2020 IMSS. Published by Elsevier Inc.
Keywords: Dental follicle; Histopathology; Mesenchymal stem cells; Immunomodulation; Sepsis; MESENCHYMAL STROMAL CELLS; ACUTE LIVER-INJURY; KIDNEY INJURY; SURVIVAL; PROTECT